Engineering chimaeric proteins from fold fragments: 'hopeful monsters' in protein design. (23rd September 2013) - Höcker, Birte
Abstract : Modern highly complex proteins evolved from much simpler and less specialized subunits. The same concept can be applied in protein engineering to construct new well-folded proteins. Hybrid proteins or chimaeras can be built from contemporary protein fragments through illegitimate recombination. Even parts from different globular folds can be fitted together using rational design methodologies. Furthermore, intrinsic functional properties encoded in the fold fragments allow rapid adaptation of the new proteins and thus provide interesting starting scaffolds for further redesign.